(3QSGFd aj af GdcJGHI hGdeNGWHGJ Hjf GdShbg hGdedhcs
(3ChdgG (B:s
(3CeG HYO , aPg QSGFd GdUOQ GdEeGe aefgG QSGdI cJHgG CHj HYV CUObGFg GdeWHNjI, cJHgG HGdObI jYQV HUOjb dg ZjQ GdecJhH Edjg hdg cJGH hYjO Edi MSGf Hf LQGM deG fgH GdQedI hNGda GdOhdI(B: (3dbO ef Ydjc CejQ GdeDefjf eQI CNQi hEf MQeJ s
(3BNQgG (B:s
(3CeG HYO , aPg QSGFd GdUOQ GdEeGe aefgG QSGdI cJHgG CHj HYV CUObGFg GdeWHNjI, cJHgG HGdObI jYQV HUOjb dg ZjQ GdecJhH Edjg hdg cJGH hYjO Edi MSGf Hf LQGM deG fgH GdQedI hNGda GdOhdI(B: (3dbO ef Ydjc CejQ GdeDefjf eQI CNQi hEf MQeJ g s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeg (B- (3GdQHGW s
Keywords: (3GdCOHs